RELIGION AS INSTITUTE OF MODERNIZATION OF SOCIETY: ANALYSIS OF POLITICAL THEORIES - Ломака, І. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In the article devoted to the analysis of political theories in relation to the social role of religion as an important institute of public relations and its value for modernization/integration of society, determination of general mechanisms of similar integration action. On the basis of complex approach of author to determination of religion role for integration of society the system of vectors of the modernization influencing of religious factor was defined, and next directions of influence were outlined: forming national consciousness, providing nationality of unity; consolidation of society round the definite ideas. On results conducted research of role of religion and church in modern society the author developed suggestions and recommendations in relation to the rise of integral role of religious factor in processes of modernization transformations.